Comparative biological properties of the four stereoisomers of difethialone, a second-generation anticoagulant rodenticide, in rats: development of a model allowing to choose the appropriate stereoisomeric ratio - Lefebvre, Sébastien; Fourel, Isabelle; Chatron, Nolan; Caruel, Hervé; Benoit, Etienne; Lattard, Virginie (Archives of toxicology, 2020)
The current management of rodent pest populations is based on second-generation anticoagulant rodenticides (SGAR). These molecules, of which difethialone is part, are much more efficient than the first generation. Nevertheless, this efficiency comes with a major drawback, SGARs are tissue persistent that increases the exposure of rodent predators to them. According to its chemical structure, difethialone has four stereoisomers, whose specific inhibition potency and pharmacokinetic have never been described and might be useful to design new eco-friendly rodenticides. The study aimed to investigate the ability to inhibit anticoagulant target enzyme (VKORC1) and the pharmacokinetics in rats of the four difethialone stereoisomers in rats. We show that stereoisomers are all highly efficient to inhibit VKORC1 activity, but they have distinct initial half-life with 6.0 h, 25.4 h, 69.3 h, and 82.3 h for, respectively, E4- trans , E2- cis , E1- trans , and E3- cis stereoisomer. These results open the way of the development of eco-friendly and efficient rodenticide by mixing some of these stereoisomers. Preferential incorporation of the E4- trans stereoisomer (high inhibitory VKORC1 potency, relatively shorter liver half-life) into difethialone rodenticides baits might result in a more eco-friendly product than current commercially available difethialone formulations. In addition, we put forward modelling to help design bait according to the circumstance of use (presence of non-target species, food competition, etc.) by modulating the theorical AUC and and the theorical concentration of the product at the death of the rodent pest. Thus, this modeling might allow to diminish the use of laboratory animal in assay. Highlights Difethialone stereoisomers are potent inhibitors of VKORC1 enzyme activity. Difethialone stereoisomer initial half-lives range from 6 to 69.3 h. E1-trans and E3-cis initial half-lives are similar and greater than other stereoisomers. Modeling can be used to refine the bait formulation process and to diminish the use of laboratory animals.